Kinerja Koperasi Berdasarkan Tingkat Kesehatan Koperasi Sesuai Permenkop. Dan UKM - Listiadi Listiadi; Sri Wahyuni Mega Hastuti (Universitas Islam Kadiri, 2020)
This research was conducted to analyze the performance of cooperatives based on the level of health of special cooperatives for savings and loan cooperatives or savings and loan units that refer to the regulation of the State Minister of Cooperatives and Small and Medium Enterprises RI Number 14 / PER / M.KUKM / XII / 2009 and the Regulation of Deputy for Supervision Ministry of Cooperatives and Small and Medium Enterprises RI number: 06 / PER. / DEP.6 / IV / 2016 by analyzing: 1) Capital 2) Earning Assets Quality 3) Management 4) Efficiency 5) Liquidity 6) Independence and Growth 7) Identity Cooperative. The object of this study is the Jasa Tirta Farmers Cooperative in Tulungagung Regency. The research method used is descriptive method with primary and secondary data. The results of the research conducted show that the health of cooperatives in 2015-2017 each scored 69.95 for 2015, a score of 70.70 for 2016 and a score of 74.95 for 2017. The determination of the level of health of the cooperative is as follows: 80 ≤ x ≤ 100 healthy predicate, 66 ≤ x <80 predicate is quite healthy, 51 ≤ x <66 predicate in supervision, and x <51 predicate in special supervision. In this assessment the health level of the Jasa Tirta Farmers Cooperative was included in the assessment category of 66 ≤ x <80 the predicate was quite healthy.